Edukasi Kesehatan Hipertensi sebagai Strategi Pencegahan Penyakit Tidak Menular Masyarakat di Wonocatur, Banguntapa, Bantul - Lina Handayani; Ika Febri Lestari; Asyifa Triandhini Setiajie; Desri Elsadiah Dangu; Shita Fitria Kaharunisa; Laely Ufiz Tsani Sugiyana; Tria Novianti (Apik Cahaya Ilmu, 2025)
Hypertension is one of the non-communicable diseases whose prevalence continues to increase and contributes significantly to morbidity and mortality in the community. Hypertension prevention efforts need to be implemented through promotive and preventive community-based approaches. This activity aimed to identify community health problems and improve public knowledge regarding hypertension in RT 04, Padukuhan Wonocatur, Banguntapan District, Bantul Regency. The method used was a community diagnosis with a quantitative descriptive design. Data were collected through questionnaires, observations, and interviews involving 45 respondents selected using purposive sampling. Problem prioritization was determined using the USG method (Urgency, Seriousness, Growth), which identified hypertension as the top health priority. The interventions included hypertension education, blood pressure screening, and elderly exercise sessions. The results of the pretest and posttest evaluations showed an increase in community knowledge after the educational intervention. Community-based hypertension education was found to be effective as a preventive effort against non-communicable diseases.